2019
DOI: 10.1002/ptr.6321
|View full text |Cite
|
Sign up to set email alerts
|

The genus Erythrina L.: A review on its alkaloids, preclinical, and clinical studies

Abstract: Erythrina L. genus (Fabaceae) comprises about 115 species, and it has been extensively studied, mainly because of its alkaloids, which have pharmacological properties. References demonstrated that Erythrina spp. have a potential to act in the central nervous system, presenting anxiolytic and anticonvulsant properties already established. Phytochemical investigations confirmed the presence of tetracyclic alkaloids as the major compounds. However, other alkaloid classes have also been reported, including dimeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 80 publications
(84 reference statements)
0
13
0
4
Order By: Relevance
“…Spectroscopic techniques such as mass spectrometry (MS), ultraviolet (UV) spectrophotometry, one-dimensional nuclear magnetic resonance (1D-NMR) spectroscopy, and its complementary techniques (heteronuclear multiple bond correlation (HMBC) spectroscopy, heteronuclear multiple quantum coherence (HMQC) spectroscopy, nuclear overhauser effect spectroscopy (NOESY), and circular dichroism (CD) spectroscopy) have been used to elucidate chemical structures of the isolated compounds [130]. Chromatography-spectroscopy hyphenated techniques have become more commonly used in recent decades due to the increased efficiency, sensitivity, and detection limits [1]. ese include LC-MS, GC-MS, UPLC-MS, HPTLC-UV, HPLC-photodiode array detection, LC- Evidence-Based Complementary and Alternative Medicine [130].…”
Section: Structural Elucidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectroscopic techniques such as mass spectrometry (MS), ultraviolet (UV) spectrophotometry, one-dimensional nuclear magnetic resonance (1D-NMR) spectroscopy, and its complementary techniques (heteronuclear multiple bond correlation (HMBC) spectroscopy, heteronuclear multiple quantum coherence (HMQC) spectroscopy, nuclear overhauser effect spectroscopy (NOESY), and circular dichroism (CD) spectroscopy) have been used to elucidate chemical structures of the isolated compounds [130]. Chromatography-spectroscopy hyphenated techniques have become more commonly used in recent decades due to the increased efficiency, sensitivity, and detection limits [1]. ese include LC-MS, GC-MS, UPLC-MS, HPTLC-UV, HPLC-photodiode array detection, LC- Evidence-Based Complementary and Alternative Medicine [130].…”
Section: Structural Elucidationmentioning
confidence: 99%
“…In the present study, we retrieved thirteen alkaloids (1-12 and 95) that have been isolated from E. abyssinica (Table 4, Figure 5). e Erythrina alkaloids have a tetracyclic carbon skeleton with three rings (A, B, and C) common to all the alkaloids and the fourth ring (D) which varies among the different alkaloids [1,152]. Lactonic alkaloids contain ring D as an unsaturated δ-lactone, dienoid alkaloids possess a benzenoid ring D (with two double bonds at C-1 and C-2, and C-6 and C-7), and alkenoid alkaloid possess a benzenoid ring D with a double bond between C-1 and C-6.…”
Section: Structural Elucidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, tannins have been identified in Portulaca oleracea [ 51 ], Chenopodium nuttalliae [ 43 , 44 , 53 ], Brassica rapa [ 61 ], Amaranthus hybridus [ 55 ] and Amaranthus cruentus [ 41 ]. In addition, Barrón-Yánez et al [ 43 ] detected the presence of saponins in Chenopodium nuttalliae , and Ibarra-Estrada et al [ 63 ] identified erisovine and erisodine alkaloids in Erythrina Americana [ 64 ]. In Begonia nelumbiifolia , Villa-Ruano et al [ 60 ] evaluated the content of oxalic acid and ascorbic acid, and in Chenopodium berlandieri , Lazo-Vélez et al [ 65 ] identified triterpenoid saponins.…”
Section: Composition Of Edible Stems Leaves and Flowers Of Quelitmentioning
confidence: 99%
“…and pharmacological properties. Many other works have analyzed the properties and effects of the Erythrina genus and we suggest that the reader examine subsequent pivotal reviews [6,7].…”
mentioning
confidence: 99%